2021
DOI: 10.1029/2021wr029890
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Advances in Mobile Mass Spectrometry Enhance Tracer Hydrology and Water Management

Abstract: New mobile mass spectrometry (MS) systems enable low-cost, high-resolution dissolved gas measurements• High-resolution sampling of dissolved gas tracers can provide new insights into hydrologic processes and systems• Combining dissolved gas measurements with other experimental and numerical methods has the potential to further hydrological research

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…New developments of in situ noble gas measurements (e.g., Ar, Kr, He) via mobile mass spectrometry (Brennwald et al., 2016) provide opportunities for improved hydrological process understanding as recently outlined by Popp et al. (2021). The usefulness of high‐frequency gas tracer measurements for transit time estimates has not yet been explored, but examples assessing the snowmelt contribution in a mountainous catchment show their feasibility (Schilling et al., 2021).…”
Section: Going Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…New developments of in situ noble gas measurements (e.g., Ar, Kr, He) via mobile mass spectrometry (Brennwald et al., 2016) provide opportunities for improved hydrological process understanding as recently outlined by Popp et al. (2021). The usefulness of high‐frequency gas tracer measurements for transit time estimates has not yet been explored, but examples assessing the snowmelt contribution in a mountainous catchment show their feasibility (Schilling et al., 2021).…”
Section: Going Forwardmentioning
confidence: 99%
“…As reviewed in Abbott et al (2016) and Sprenger et al (2019), introducing tracers that are more commonly used in groundwater age dating, like CFCs, SF 6 or 85 Kr, can constrain the parameter space accounting for the long tails in transit time modeling (i.e., old water contributions to stream discharge). New developments of in situ noble gas measurements (e.g., Ar, Kr, He) via mobile mass spectrometry (Brennwald et al, 2016) provide opportunities for improved hydrological process understanding as recently outlined by Popp et al (2021). The usefulness of high-frequency gas tracer measurements for transit time estimates has not yet been explored, but examples assessing the snowmelt contribution in a mountainous catchment show their feasibility (Schilling et al, 2021).…”
Section: What We Need From New Field Work and Tracer Techniquesmentioning
confidence: 99%
“…with hydrochemical data has great potential to further system understanding of surface water-groundwater interactions and associated biogeochemical cycling (Popp, Manning, & Knapp, 2021;Popp, Pardo-Alvarez, et al, 2021;Popp, Scheidegger, et al, 2019). • Machine learning approaches: The data can serve as a foundation for the development and validation of machine learning models (e.g., Maier et al, 2010;Tyralis et al, 2019).…”
Section: Results and Brief Discussion Of The Datamentioning
confidence: 99%
“…Moreover, the data can be used for model calibration and validation by reducing parameter uncertainty and thereby improving the predictive capacity of the chosen model. Research has shown that hydraulic heads alone do not contain sufficient information to calibrate flow models (Moeck et al., 2020; Schilling et al., 2019), consequently, combining hydraulic with hydrochemical data has great potential to further system understanding of surface water‐groundwater interactions and associated biogeochemical cycling (Popp, Manning, & Knapp, 2021; Popp, Pardo‐Alvarez, et al., 2021; Popp, Scheidegger, et al., 2019). Machine learning approaches: The data can serve as a foundation for the development and validation of machine learning models (e.g., Maier et al., 2010; Tyralis et al., 2019).…”
Section: Results and Brief Discussion Of The Datamentioning
confidence: 99%